Trace elements bioaccumulation in liver and fur of Myotis myotis from two caves of the eastern side of Sicily (Italy): A comparison between a control and a polluted area. (September 2018) - Ferrante, Margherita; Spena, Maria Teresa; Hernout, Béatrice Veronique; Grasso, Alfina; Messina, Andrea; Grasso, Rosario; Agnelli, Paolo; Brundo, Maria Violetta; Copat, Chiara
Abstract: Environmental pollution is a topic of great interest because it directly affects the quality of ecosystems and of all living organisms at different trophic and systematic levels. Together with the global climate change, the long-term surviving of many species of plants and animals is threaten, distributional patterns at global and regional levels are altered and it results in local assemblages of species that are quite different from those that currently constitute coevolved communities. .For this study, the species Myotis myotis was used as bioindicator and it was sampled from two caves in the south-east of Sicily, Pipistrelli chosen as control area and Palombara chosen as polluted area, to measure the concentrations of trace elements in fur and liver tissues. Results showed higher content of essential elements in fur in bats sampled from Pipistrelli. Conversely, higher concentrations of toxic metals in liver such as As, Cd, Pb and Hg were measured in bat samples in Palombara cave, where specimens have a hunting area extended within the boundaries of the petrochemical plant. Nevertheless, we cannot consider Palombara population as polluted by metal contamination since their tissue concentrations are overall lower than toxic thresholds values suggested for small mammals. Likewise, we cannot exclude other kind of pollutants as potential stressors of the examined population, contributing with the decreasing of bat colonies in Sicily. Graphical abstract: Image Highlights: Bats were sampled from Pipistrelli cave chosen as control area and Palombara cave chosen as polluted area. Trace elements were analysed in fur and liver. Results showed a better health status in bats sampled from Pipistrelli cave. Bats sampled in Palombara cave were found with higher concentrations of toxic metals. Metals are in the range or lower than toxic thresholds or upper range values. Abstract : Bats sampled in Palombara cave revealed a greater chronic exposure to toxic metals than specimens sampled in Pipistrelli cave. Nevertheless, metal concentrations are in the range than other literature findings and lower than toxic thresholds or upper range values suggested for small mammals.